Conversion of hydrogen to ammonia as a method of increasing energy density – a simulation study - Miller, Michalina; Nowacki, Karol P.; Kopiński, Maciej; Zmyślony, Michał; Wasilewska, Alicja; Mitkowski, Piotr T.; Woziwodzki, Szymon (Chemical and Process Engineering: New Frontiers, 2026)
In light of the current efforts of harnessing hydrogen as a potential carbon free energy source alternative to fossil fuels, ammonia has emerged as one of the possible candidates for an effective hydrogen storage method, due to its significantly simplified storage conditions. In this work, the Haber-Bosch process for ammonia synthesis was studied for three scales of production, in the aspect of energy efficient reactor design and optimal operational conditions, with the use of a process simulator, allowing for the manipulation of desired plant parameters in a wide range of values. Moreover, the energy balance of the process has been included in the research process allowing for the visualization of energetic cost of increasing the energy density of the system. The obtained data provides a basis for analysing the Haber-Bosch process in the context of ammonia conversion for hydrogen storage.